Metabolism of Pentose Sugars in the Hyperthermophilic Archaea Sulfolobus solfataricus and Sulfolobus acidocaldarius - Nunn, Charlotte E. M. (American Society for Biochemistry and Molecular Biology, 2010)
We have previously shown that the hyperthermophilic archaeon, Sulfolobus solfataricus, catabolizes d-glucose and d-galactose to pyruvate and glyceraldehyde via a non-phosphorylative version of the Entner-Doudoroff pathway. At each step, one enzyme is active with both C6 epimers, leading to a metabolically promiscuous pathway. On further investigation, the catalytic promiscuity of the first enzyme in this pathway, glucose dehydrogenase, has been shown to extend to the C5 sugars, d-xylose and l-arabinose. In the current paper we establish that this promiscuity for C6 and C5 metabolites is also exhibited by the third enzyme in the pathway, 2-keto-3-deoxygluconate aldolase, but that the second step requires a specific C5-dehydratase, the gluconate dehydratase being active only with C6 metabolites. The products of this pathway for the catabolism of d-xylose and l-arabinose are pyruvate and glycolaldehyde, pyruvate entering the citric acid cycle after oxidative decarboxylation to acetyl-coenzyme A. We have identified and characterized the enzymes, both native and recombinant, that catalyze the conversion of glycolaldehyde to glycolate and then to glyoxylate, which can enter the citric acid cycle via the action of malate synthase. Evidence is also presented that similar enzymes for this pentose sugar pathway are present in Sulfolobus acidocaldarius, and metabolic tracer studies in this archaeon demonstrate its in vivo operation in parallel with a route involving no aldol cleavage of the 2-keto-3-deoxy-pentanoates but direct conversion to the citric acid cycle C5-metabolite, 2-oxoglutarate.